Development of a Machine for Cleaning the Core of Grass Straws - Nguyen, Ngoc-Kien; Nguyen, Hai-Nam; Nguyen, Van-Tinh (Engineering, Technology & Applied Science Research, 2024)
Nowadays, plastic waste is one of the most pressing issues, especially in developing countries. Plastic waste comes from everyday products such as plastic food boxes, plastic bottles, disposable products, or plastic straws causing negative effects on the environment. On the other hand, grass straws are eco-friendly and safe and can be easily found in Southeast Asian countries such as Vietnam, Indonesia, and Malaysia. However, the process of grass straw production is implemented manually, resulting in low productivity and unsafe labor conditions. Among the stages of producing grass straws, cleaning the core of the straw is the most important because it determines its quality. Aiming to automate the grass straw production process, this paper introduces the first grass straw core cleaning machine in the world.